Bacterial Strategies to Preserve Cell Wall Integrity Against Environmental Threats - Yadav, Akhilesh K.; Espaillat, Akbar; Cava, Felipe (Frontiers in Microbiology, 2018)
Bacterial cells are surrounded by an exoskeleton-like structure, the cell wall, composed primarily by the peptidoglycan sacculus. This structure is made up of glycan strands cross-linked by short peptide generating a covalent mesh that shapes bacteria and prevents their lysis due to their high internal osmotic pressure. Even though the peptidoglycan is virtually universal in bacteria, there is a notable degree of diversity in its chemical structure. Modifications in both the sugars and peptides are known to be instrumental for bacteria to cope with diverse environmental challenges. In this review, we summarize and discuss the cell wall strategies to withstand biotic and abiotic environmental insults such as the effect of antibiotics targeting cell wall enzymes, predatory peptidoglycan hydrolytic proteins and peptidoglycan signaling systems. Finally we will discuss the opportunities that species-specific peptidoglycan variability might open to develop antimicrobial therapies.